[fam‐] trastuzumab deruxtecan, antitumor activity is dependent on HER2 expression level rather than on HER2 amplification. Issue 12 (24th May 2019) - Takegawa, Naoki; Tsurutani, Junji; Kawakami, Hisato; Yonesaka, Kimio; Kato, Ryoji; Haratani, Koji; Hayashi, Hidetoshi; Takeda, Masayuki; Nonagase, Yoshikane; Maenishi, Osamu; Nakagawa, Kazuhiko
Abstract : Therapies targeted to human epidermal growth factor receptor 2 (HER2) have proven effective against tumors positive for HER2 amplification, but there is an unmet clinical need for the treatment of tumors that express HER2 protein in the absence of HER2 amplification. [fam‐] trastuzumab deruxtecan (DS‐8201a) is a novel antibody–drug conjugate composed of the anti‐HER2 antibody and the topoisomerase I inhibitor, an exatecan derivative. It has shown efficacy against tumors that express HER2 and is currently under evaluation in clinical trials. We here show that the antitumor activity of [fam‐] trastuzumab deruxtecan is dependent on the expression level of HER2 protein in colorectal cancer (CRC) cell lines negative for HER2 amplification. We established isogenic CRC cell lines that express various levels of HER2 protein in the absence of HER2 amplification, and we found that cells that express HER2 at a high level were sensitive to [fam‐] trastuzumab deruxtecan but not to conventional HER2‐targeted therapies. Furthermore, [fam‐] trastuzumab deruxtecan manifested a bystander killing effect both in vitro and in vivo, with cells essentially negative for HER2 expression also being killed in the presence of HER2‐expressing cells, an effect that has the potential to overcome heterogeneity of HER2 expression in CRC tumors. Our results thus suggest that [fam‐] trastuzumab deruxtecan warrants further study as a potential treatment for CRC tumors that express HER2 protein in the absence of HER2 amplification. Abstract : What's new? HER2‐targeted therapies have proven effective against tumors positive for HER2 amplification, but there is an unmet clinical need for tumors that express HER2 in the absence of HER2 amplification. [fam‐] trastuzumab deruxtecan (DS‐8201a) is a novel antibody‐drug conjugate composed of the anti‐HER2 antibody and the topoisomerase I inhibitor. Here, DS‐8201a showed efficacy on colorectal cancer (CRC) cell lines that express HER2 in the absence of HER2 amplification. Furthermore, [fam‐] trastuzumab deruxtecan exhibited a bystander killing effect in co‐culture models of HER2‐expressing cells and HER2‐negative cells. The results may offer a new treatment option against CRC according to HER2 expression levels.